Exponential moments of first passage times and related quantities for Lévy processes. Issue 17 (23rd June 2015) - Aurzada, Frank; Iksanov, Alexander; Meiners, Matthias
Abstract : For a Lévy process on the real line, we provide complete criteria for the finiteness of exponential moments of the first passage time into the interval ( r, ∞ ), the sojourn time in the interval ( − ∞, r ], and the last exit time from ( − ∞, r ] . Moreover, whenever these quantities are finite, we derive their respective asymptotic behavior as r → ∞ .